2002
DOI: 10.1191/1358863x02vm452oa
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies in thromboangiitis obliterans

Abstract: Thromboangiitis obliterans (TAO) and antiphospholipid syndrome (APS) share the clinical characteristics of arterial thrombosis and recurrent thrombophlebitis. Although the association of anticardiolipin antibodies (aCLa) and TAO has been previously recognized, the prevalence and the clinical impact of this association remains unclear. aCLa were measured by double ELISA in patients with TAO (n=47), premature atherosclerosis (pASO) (n=48) and otherwise healthy individuals (n=48). Antibody status was then compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…Maslowski et al suggested that anticardiolipin antibodies are important for the pathogenesis of Buerger disease patients [14]. Patients with generalized periodontitis had a significantly greater prevalence of IgG or IgM anticardiolipin antibodies, and these antibodies were significantly higher in smoker than non-smoker patients [15].…”
Section: Discussionmentioning
confidence: 98%
“…Maslowski et al suggested that anticardiolipin antibodies are important for the pathogenesis of Buerger disease patients [14]. Patients with generalized periodontitis had a significantly greater prevalence of IgG or IgM anticardiolipin antibodies, and these antibodies were significantly higher in smoker than non-smoker patients [15].…”
Section: Discussionmentioning
confidence: 98%
“…In this issue of Vascular Medicine, Maslowski and colleagues 6 report on the association of elevated anticardiolipin antibodies (aCLa) in 47 patients with thromboangiitis obliterans who were evaluated between 1990 and 1996. Using a double antibody sandwich enzyme-linked immunosorbent assay (ELISA) and reporting the data as an antibody-binding index (BI), the investigators reported a prevalence of elevated aCLa in 36% of patients with Buerger's disease compared to 8% of patients with premature atherosclerosis and 2% of healthy controls.…”
mentioning
confidence: 99%
“…Several studies have focused on the presence of antiphospholipid antibodies (Casellas et al 1993). A report on 47 patients with TAO, 48 patients with juvenile atherosclerosis and 48 healthy subjects showed that antiphospholipid antibodies are more elevated (36%) in TAO patients than in patients with juvenile atheroma (8%, p = 0.01) or healthy subjects (2%, p \ 0.001) (Maslowski et al 2002). However, these studies had numerous methodological limitations, and other observations are necessary to confirm this hypothesis (Olin 2002).…”
Section: Aetiologymentioning
confidence: 97%